Даурия: [роман] / Константин Седых - Седых Константин Федорович (Сибириада, 2021)
Экземпляры: 5 (20240515) / Инвентарный номер: 57321 / Цена: 498.00 / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: С 28 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=411.2)6